2015
DOI: 10.1007/s11306-015-0880-x
|View full text |Cite
|
Sign up to set email alerts
|

The pretransplant systemic metabolic profile reflects a risk of acute graft versus host disease after allogeneic stem cell transplantation

Abstract: Allogeneic stem cell transplantation is used in the treatment of younger patients with severe hematological diseases, especially hematological malignancies, and acute graft versus host disease (GVHD) is then an important immune-mediated posttransplant complication. Several risk factors for acute GVHD have been identified, including pretransplant factors that possibly influence the posttranspant course through their effects on host immunocompetent cells. Metabolic regulation is important for immunoregulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…Several metabolites that show different levels are known to induce endothelial dysfunction or altered vascular and renal functions. We have previously described that pretransplant factors reflect the risk of acute GVHD after allotransplantation [ 8 , 65 ], and our present observations suggest that pretransplant metabolic factors are important also for the risk of posttransplant fluid retention.…”
Section: Discussionsupporting
confidence: 72%
“…Several metabolites that show different levels are known to induce endothelial dysfunction or altered vascular and renal functions. We have previously described that pretransplant factors reflect the risk of acute GVHD after allotransplantation [ 8 , 65 ], and our present observations suggest that pretransplant metabolic factors are important also for the risk of posttransplant fluid retention.…”
Section: Discussionsupporting
confidence: 72%
“…GVHD target organs show differential kinetic and often discordant progression and vary in cytokine profiles among themselves, despite an allogeneic T cell response being considered the driving cause (Kumar et al, 2017). Figure 2 shows the phases of GVHD pathophysiology with immunoregulatory aspects -modified from Ferrara et al, 2009. Metabolic regulation is important for immunoregulation and GVHD, and pretransplant cytokine profiles and metabolic status of allotransplant recipients are shown to be associated with a risk of later a GVHD development (Reikvam et al, 2016). Previous studies suggest differences in immune cells metabolism and may FIGURE 2 | Schematic overview of graft vs. host disease (GVHD) pathophysiology with immunoregulatory aspects: Conditioning regimen at the time of transplant causes damage to the host tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of multiple markers of inflammation and oxidative stress were increased in our cGVHD patients ( 36 ), possibly reflecting an increased risk of inflammatory complications after allo-HSCT. Uremic toxicity, metabolic acidosis, and pro-inflammatory soluble mediators may activate protein degradation in cGVHD ( 25 , 32 , 49 ), and cGVHD may thereby be associated with altered metabolic and endocrine functions of several organs ( 8 , 31 , 36 ). An altered balance between protein synthesis and catabolism may then be the final result.…”
Section: Discussionmentioning
confidence: 99%
“…Graft versus host disease can be considered an exaggerated manifestation of normal inflammatory mechanisms in which donor lymphocytes encounter foreign antigens in a pro-inflammatory milieu, and this inflammation involves several donor immunocompetent cell subsets ( 8 , 9 , 20 22 ). Metabolic regulation is important for immunoregulation, and we have previously demonstrated that pretransplant cytokine profiles as well as the pretransplant metabolic status of allotransplant recipients is associated with a risk of later aGVHD ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%